French Lessons in Late-Medieval England The "Liber Donati" and "Commune Parlance" (Arc Humanities Press, 2023)
French Lessons in Late-Medieval England presents two fifteenth-century manuals designed to support facility in French among the English, the Liber donati and Commune parlance. These texts treat the grammar, lexis, and orthography of French as well as compiling a selection of entertaining dialogues that model the language in action. Together, they paint a vivid picture of the kinds of French that English learners might desire to wield and of the high levels of fluency that they could achieve. Critten's comprehensive introduction discusses his materials' relevance both for histories of language education and for recent reassessments of the longevity of French in medieval England. His pairing of first-time modern-English translations with facing-page original text makes these fascinating works newly available for a twenty-first-century audience.